2021
DOI: 10.1039/d1bm00370d
|View full text |Cite
|
Sign up to set email alerts
|

Theranostic potential of biodegradable polymeric nanoparticles with paclitaxel and curcumin against breast carcinoma

Abstract: Self-assembled theranostic hybrid nanoparticles containing dual drugs showed a specific targeting ability for breast carcinoma, and significantly reduced the tumor size due to the synergistic effects of the dual drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Moreover, the CI values were even lower for PLGA-CUR-PTX nanoparticles, with 0.17 on 4T1 cells and 0.20 on MCF-7 cells, which demonstrated the good synergistic antitumor effect of CUR and PTX. Moreover, CUR and PTX coloaded PLGA nanoparticles had the lowest IC 50 values on 4T1 (CUR: 123.7 ng/mL; PTX: 66.7 ng/mL) and MCF-7 (CUR: 109.9 ng/mL; PTX: 59.37 ng/mL) cells, which were similar with the previous report . In this study, CUR combined with PTX could decline the IC 50 of both CUR and PTX.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the CI values were even lower for PLGA-CUR-PTX nanoparticles, with 0.17 on 4T1 cells and 0.20 on MCF-7 cells, which demonstrated the good synergistic antitumor effect of CUR and PTX. Moreover, CUR and PTX coloaded PLGA nanoparticles had the lowest IC 50 values on 4T1 (CUR: 123.7 ng/mL; PTX: 66.7 ng/mL) and MCF-7 (CUR: 109.9 ng/mL; PTX: 59.37 ng/mL) cells, which were similar with the previous report . In this study, CUR combined with PTX could decline the IC 50 of both CUR and PTX.…”
Section: Resultsmentioning
confidence: 99%
“…The mean diameter and polydispersity index (PDI) of micelles formed in hydrogel precursor solutions were characterized by DLS (Zetasizer Nano ZS; Malvern Instruments, Malvern, UK) 55 . A specific concentration of solution (2 mg/mL) was immersed in Polystyrene Disposable Cells (Q-VETTES Semi-micro; Ratiolab, Frankfurt, Germany) and measured at 25 °C.…”
Section: Methodsmentioning
confidence: 99%
“…4T1 tumor-bearing mice were used to evaluate the anti-tumor efficacy of Cur@HFn in vivo (Kim et al., 2021 ; Yu et al., 2021 ). Female mice were inoculated with a suspension of 4T1 cells in physiological saline (100 μL, 1 × 10 6 cells) into the right mammary gland.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, a plethora of cytotoxicity and animal experiments have shown that Cur has good anti-cancer activity, especially in the treatment of breast cancer, prostate cancer, lung cancer, and ovarian cancer (Ma et al., 2019 ). Its mechanism is to inhibit P-gp and down-regulate nuclear factor kappa-light-chain-enhancer of activated B cell (NF-κB) and phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt) pathways, inducing apoptosis by suppressing the growth of cancer cells (Kim et al., 2021 ). Clinical trials have proved that Cur has few side effects and high safety, and the safe dose can be as high as 12 g per day (Kumari et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%